THE EFFECTIVENESS OF PREMARITAL MARRIAGE GUIDANCE (ISLAMIC EDUCATION GUIDANCE MODEL) IN REDUCING THE HIGH DIVORCE RATE IN KUA NORTH SUMATERA PROVINCE - Harahap, Rafnitul Hasanah; Asmuni, Asmuni; Khoiri, Nisful (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
Decree of the Director General of Islamic Community Guidance No. 379 of 2018 concerning the Implementation of Premarital Marriage Guidance, which aims to create a happy and peaceful family and reduce the divorce rate But in reality, in the city of Medan, the divorce rate continues to increase every year. This study focuses on the issue of implementing premarital marriage guidance based on the Decree of the Director General of Islamic Community Guidance Number 379 of 2018 at the KUA in Medan City, as well as the extent of the impact of fostering premarital marriages. based on the Decree of the Director General of Islamic Community Guidance No. 379 of 2018 concerning reducing the divorce rate in Medan City. The research model (mode of inquiry) is a type of qualitative research oriented to field research (empirical), which is related to the Islamic education approach and premarital guidance. The results of the research are oriented towards the effectiveness of coaching and education for premarital marriages that are not working as well as they should. There are still many married couples who do not get premarital marriage guidance but get a marriage certificate, and premarital marriage coaching should be an administrative requirement by showing proof of marriage certificate for couples who are getting married. There is also a lack of understanding of the implementation of Islamic educational values, and the government must give authority to the KUA as a follow-up to premarital marriage development activities to mediate between married couples who are about to divorce before going to the Religious Courts.